The Climate Security Sensitiveness Tool (CSST) - Sahel template - Sarzana, Carolina; Pacillo, Grazia; Läderach, Peter R.D. (2022)
The CSST is a programming assessment tool for conflict-sensitive and peace-responsive climate action, which can be used at the designing phase of a program. The tool is employed on the premise any fragile context is characterized by a unique set of risk factors for crises, including human and natural hazards, socioeconomic vulnerabilities, vulnerable groups, and low institutional and infrastructural coping capacity, which can be addressed by climate-peace mechanisms, namely economic development, building institutions, building trust and cooperation, resource sustainability, enhancing knowledge and building capacity and resilience. It aims to test the suitability of agricultural climate adaptation programs in relation to these pre-existing risk factors, referred to as drivers of conflict and insecurity, and to formulate recommendations on how they can do so more effectively. It does so by projecting an ideal set of climate-peace mechanisms for that context next to the set of mechanisms currently delivered by the proposed program design, allowing practicioners to re-define their intervention in order to match the ideal mechanisms.